Juan de Moctezuma y Cortés: el ascenso al poder de un cacique indígena (Tepexi de la Seda, 1703-1778) - Cruz Pazos, Patricia (Revista Española de Antropología Americana, 2008)
This paper analyses Juan de Moctezuma and Cortés’ figure, the most powerful cacique of Tepexi de la Seda during eighteenth century, in order to tackle what conditions he had and what strategies he developed to attain that position.